Charge Transport through Peptides in Single‐Molecule Electrical Measurements. Issue 10 (6th September 2019) - Zheng, Haining; Jiang, Feng; He, Runze; Yang, Yang; Shi, Jia; Hong, Wenjing
Abstract : Charge transport across the peptide chains is one of the vital processes in the biological systems, so understanding their charge transport properties is an indispensable prerequisite to explain the complex biochemical phenomenon. Here, we review the charge transport mechanism, the influence of the special groups and the experimental conditions on the charge transport through the peptide backbone by employing the single‐molecule electrical measurements. Besides, we further review the recent progresses in charge transport properties of supramolecular interaction among the adjacent peptide chains. Finally, we discuss some experimental and theoretical contradictions existing in the charge transport through peptides and provide new inspiration for the future development of the bioelectronics at the single‐molecule scale. Abstract :